1984
DOI: 10.1161/01.hyp.6.2_pt_2.i7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a radioiodinated photoaffinity probe for the alpha 1-adrenergic receptor.

Abstract: A radioiodinated aryl azide analog, 2-[4-(4-azido-3- iodobenzoyl ) piperazin -1-yl]-4-amino-6, 7- dimethoxyquinazoline [(125I] CP65 ,526), of the highly selective alpha 1-adrenergic antagonist prazosin was synthesized and characterized using rat hepatic plasma membranes. Prior to photolysis, this ligand bound with high affinity (Kd 0.3 nM), stereoselectively and in a saturable manner to sites with an alpha 1-adrenergic specificity. When membranes pretreated with [125I] CP65 ,526 were irradiated with ultraviole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Much work has gone into modifying the structure of the basic prazosin molecule to retain selective a-1 blockade but obtain a longer, more gradual action. Seidman and colleagues (84) found a photoaffinity a-1 selective probe to characterize the a-1 adrenoceptor, which demonstrated that the group in the N-4 position of the piperazine moiety was unnecessary for activity; similarly, Timmermans e t al. (85), reported that a piperidine derivative had potent a-1 inhibitory activity.…”
Section: Structure-function Relationships I N Quinazoline A-blockadementioning
confidence: 95%
See 1 more Smart Citation
“…Much work has gone into modifying the structure of the basic prazosin molecule to retain selective a-1 blockade but obtain a longer, more gradual action. Seidman and colleagues (84) found a photoaffinity a-1 selective probe to characterize the a-1 adrenoceptor, which demonstrated that the group in the N-4 position of the piperazine moiety was unnecessary for activity; similarly, Timmermans e t al. (85), reported that a piperidine derivative had potent a-1 inhibitory activity.…”
Section: Structure-function Relationships I N Quinazoline A-blockadementioning
confidence: 95%
“…Although doxazosin is also found to have a longer half-life than prazosin, the benzodioxan moiety may not be as water-soluble as the tetrahydrofuran group in terazosin. There is a benzodioxan double-ring in the simple a-blocker piperoxan, but the exact identity of the substitute seems unimportant (84)(85)(86)(87).…”
Section: Once-daily Q U I N a Z O L I N E A-1 A D R E N O C E P T O Rmentioning
confidence: 99%
“…Iodoazidoaryl prazosin (IAAP), a photoactive analog of prazosin, has been previously reported to act as a multidrug resistance reversal agent by binding and inhibiting Pgp1 function [90]. As the synthesis of IAAP following the earlier route [91] proved to be dangerously unreliable, a convergent route involving direct addition of an acylated piperazine to 2-chloroquinazoline intermediate was established [92]. Erlotinib can also inhibit multidrug resistance by reversing ABC subfamily B member 1 (ABCB1; P-glycoprotein) and ABC subfamily G member 2 (ABCG2; breast cancer resistance protein/mitoxantrone resistance protein) functions in cancer cells through direct inhibition of the drug efflux function of ABCB1 and ABCG2 [93].…”
Section: Therapeutic Targeting Of Adrenoceptorsmentioning
confidence: 99%